2005
DOI: 10.1007/s11064-005-2677-1
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Copper Transporter in Lead-induced Oxidative Stress in Astroglia

Abstract: Lead (Pb), depositing primarily in astroglia in the brain, is a well-known neurotoxicant and a risk factor for neurologic disorders. Pb has been reported to induce oxidative stress by probably the disturbance of copper (Cu) homeostasis in astroglia. Thus, we hypothesized that Pb-induced oxidative stress is initiated by interfering with Cu transporter in astroglia. In this study, we observed Pb-induced oxidative stress as indicated by reactive oxygen species (ROS) augmentation and GRP78 and GRP94 protein induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 40 publications
(71 reference statements)
1
31
0
Order By: Relevance
“…ATP7A is known to bind other metals such as silver (Cobine et al, 2000), and the metallochaperone Atx1 has been shown to deliver cadmium and mercury to CCC2, the ATP7B equivalent in yeast (Morin et al, 2004). It has also been reported recently that ATP7A is capable of conferring resistance to lead in astroglia in a manner that required the metal binding domains of this protein (Qian et al, 2005). ATP7B is found in the membranes of secretory vesicles, and it can clearly mediate resistance to DDP and enhance its intracellular sequestration (Safaei, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…ATP7A is known to bind other metals such as silver (Cobine et al, 2000), and the metallochaperone Atx1 has been shown to deliver cadmium and mercury to CCC2, the ATP7B equivalent in yeast (Morin et al, 2004). It has also been reported recently that ATP7A is capable of conferring resistance to lead in astroglia in a manner that required the metal binding domains of this protein (Qian et al, 2005). ATP7B is found in the membranes of secretory vesicles, and it can clearly mediate resistance to DDP and enhance its intracellular sequestration (Safaei, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Astrocyte cultures were established using a modification of methods described by (Guilian and Baker, 1986) and (Lehnardt et al, 2002), expert advice from Dr. E. Tiffany-Castiglioni (Lindahl et al, 1999;Qian et al, 2005) and a previously established laboratory protocol (Johnson and Sohrabji, 2005). The experimental protocol is similar to those used in other published studies using astrocyte cultures .…”
Section: Tissue Culture -Astrocytesmentioning
confidence: 99%
“…This may suggesting that N application would result in more biomass production by increasing the photosynthetic rate (Landberg and Greger 2003) It have been reported that heavy metal stress induced by Cd generate Reactive Oxygen Species (ROS) production in plants which lead to different damages. Lipid peroxydation is considered as the most damaging process known to occur due to ROS production (Qian et al, 2005). Our results showed that TBARS content is two times higher in shoots than in roots.…”
Section: Discussionmentioning
confidence: 46%
“…Antioxidants play an important role in adaptation and ultimate survival of plants under heavy metal stress conditions (Qian et al, 2005). One of the protective mechanisms is the enzymatic antioxidant system, which involves catalase (CAT), an enzyme which catalyses hydrogen peroxide (H 2 O 2 ) dismutation into oxygen(O 2 ) and water (H 2 O) (Sun and Zhou 2008) Our results indicate that CAT activity significantly increased in shoots of plants exposed to Cd combined with PK fertilization.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation